Bioactive Compounds Constituent and Anti-Inflammatory Activity of Natural Rice Bran Oil Produced from Colored and Non-Pigmented Rice in Northern Thailand - Thanawat Pattananandecha; Jakkapan Sirithunyalug; Busaban Sirithunyalug; Kannika Thiankhanithikun; Chartchai Khanongnuch; Chalermpong Saenjum (Journal of Pharmacy and Nutrition Sciences, 2019)
The aims of the study were to measure and compare the content of the bioactive compounds in natural rice bran oils (NRBOs) and investigate for anti-inflammatory activity through inhibition effect on nitric oxide (NO) and inducible nitric oxide synthase (iNOS) in RAW264.7 mouse macrophage cells.NRBOs were prepared from colored and non-pigmented rice in northern Thailand using the cold-press technique. The bioactive compound constituents in NRBOs, including tocotrienols, tocopherols, and γ-oryzanol were analyzed by reversed-phase HPLC. Then, anti-inflammatory activity was investigated through an inhibition effect on NO and iNOS production induced by combined lipopolysaccharide (LPS)-interferon-γ (IFN-γ) in RAW264.7 mouse macrophage cells. The results demonstrated that NRBOs prepared from purple rice, red rice and non-pigmented rice consist of δ, γ, and α-tocotrienol, δ, β, γ, and α-tocopherol, and γ-oryzanol. γ-Oryzanol, γ-tocotrienol, and γ-tocopherol were the major bioactive compounds in NRBOs. NRBOs prepared from purple rice bran exhibited higher concentrations of the bioactive compounds than red rice bran and non-pigmented rice bran, respectively. Khaoʹ′ GamLeum-Phua (KGLP) exhibited the highest amount of δ, γ and α-tocotrienol, δ, γ, β and α-tocopherol, and γ-oryzanol. Interestingly, all NRBOs inhibited NO and iNOS production by LPS/IFN-γ-stimulated RAW264.7 cells. Additionally, NRBO prepared from KGLP exhibited the highest inhibitory activity on NO and iNOS production. There may a potential use for pigmented NRBOs especially cultivated in mountainous areas which containing high amounts of tocotrienols, tocopherols, and γ-oryzanol, as a natural anti-inflammatory active ingredient in nutraceutical and cosmeceutical products.